Effective minority carrier lifetime and distribution of steady-state excess minority carriers in macroporous silicon - V. F. Onyshchenko; L. A. Karachevtseva (Хімія, фізика та технологія поверхні, 2017)
We have obtained a simple expression that determines the effective minority carrier lifetime in macroporous silicon with periodic arrangement of infinitely long macropores as a function of bulk lifetime, surface recombination velocity of minority carriers, pore radius and the distance between the centers of macropores. This expression can be applied also to macroporous silicon with randomly distributed pores by replacing the pore radius and the distance between the centers of macropores with their average values. The distribution of steady-state excess minority carriers in macroporous silicon is calculated for the analytical model proposed by us. The calculation is made for the case when both the outer surface of macroporous silicon and the bottom of pores are illuminated with light. We observed two peaks of the distribution of steady-state excess minority carriers in macroporous silicon near the surfaces illuminated with light of wavelength 0.95 ?m. At the same time, if macroporous silicon was illuminated with light with the wavelength of 1.05 ?m, we observed only one maximum in the distribution function of the excess minority carriers, in spite of the fact that the pore bottom was also illuminated with light. It is shown that the distribution of excess minority carriers in macroporous silicon with through pores is similar to the distribution in single crystal silicon. But in this case, the effective lifetime of minority charge carriers in the effective medium of macroporous silicon, which includes silicon and the surface of pores, corresponds to the bulk minority-carrier lifetime in monocrystalline silicon.